The experience of İstanbul Protocol: efficiency, quality,_x000D_ difficulties in practice - TURAN YURTSEVER, NURŞEN (My University, 2019)
Objectives: Physicians who witness torture and ill treatment can be placed in a difficult position if theirevidence was not accurately documented. The guidelines and ethical codes of the Istanbul Protocol requiredoctors to attend first and foremost to the well-being of their patients and to remain bound by the principles ofmedical ethics. The objective of this study was to compare the efficiency and the quality of the examination ofdetainees or alleged torture cases by medical doctors and the difficulties encountered in this activity.Methods: A questionnaire was developed and sent to physicians in Black Sea Shore region of Turkey beforeand 1 year after their receiving training according to the Istanbul Protocol.Results: There were 42 physicians who had undergone training according to the Istanbul Protocol and hadanswered the questionnaire; 28.6% of these were women and 71.4% men. These physicians applied the IstanbulProtocol more frequently after having received training on the Protocol Manual as compared to before thetraining. The 52.4% of these physicians reported having been the object of violence or intimidation.Conclusions: It was determined that the physicians' knowledge of physical and psychological examinationincreased following their training according to the Istanbul Protocol.